Long-term Euro-ASA Registry Data - Cunningham, Muriel (MD Conference Express, 2015)
Alcohol septal ablation (ASA) performed in dedicated centers is a safe and effective procedure for highly symptomatic obstructive hypertrophic cardiomyopathy patients. The post-ASA residual obstruction is a significant factor influencing long-term functional status and survival. Appropriate pre-procedural patient selection and elimination of the left ventricular outflow obstruction should be pursued in these patients.